(untitled) (Cambridge, UK, 2001)
The book provides an authoritative review of key procedures in the frying process, especially as regards improving quality in the manufacture of fried products such as ready-made meals and snack foods. Looks at the role of frying oil, and examines the impact of frying on lipid intake.
Keywords: Frying,Oils and fats, edible